Pemasaran Digital Berbasis Data di Abad ke-21: Tinjauan Strategi, Teknologi, dan Dampaknya terhadap Konsumen - Yuliansyah Al Rasyid; Ariawan Aryapranata; Yogi Priya Agsena; Rizky Okta Darmawan (Institut Bisnis Nusantara, 2026)
Digital marketing has transformed how organizations engage consumers, measure marketing performance, and allocate resources efficiently. This study synthesizes contemporary scholarship on digital marketing, covering social media, search engines, content marketing, influencer activities, e-commerce, and analytics-driven strategies. The research aims to examine definitions and evolution, channels and tactics, data-driven decision making, digital consumer behavior, sectoral applications, and sustainability considerations. A systematic literature review of recent peer-reviewed publications was conducted. Findings indicate that digital marketing constitutes an interactive, personalized, and measurable multi-channel ecosystem. Social media and influencer strategies significantly enhance engagement and purchase intention, while SEO/SEM and analytics improve visibility and return on investment. CRM integration strengthens customer loyalty and retention. However, effectiveness varies across industries, cultural contexts, and digital maturity. Data privacy, security, and sustainability concerns also emerge as critical challenges. The study concludes that successful digital marketing requires channel integration, audience-centric content, advanced analytics, and ethical data governance. The findings provide practical implications for practitioners and suggest directions for future research, including long-term ROI measurement, cross-cultural comparisons, and sustainability metrics.